Serological survey of antibodies against Toxoplasma gondii in organic sheep and goat farms in Greece - NTAFIS (Β. ΝΤΑΦΗΣ), V.; XYLOURI (Ε.Μ. ΞΥΛΟΥΡΗ), E.; DIAKOU (Α. ΔΙΑΚΟΥ), A.; SOTIRAKOGLOU (Α. Κ. ΣΩΤΗΡΑΚΟΓΛΟΥ), K.; KRITIKOS (Ι. ΚΡΗΤΙΚΟΣ), I.; GEORGAKILAS (Ε. ΓΕΩΡΓΑΚΙΛΑΣ), E.; MENEGATOS (Ι. ΜΕΝΕΓΑΤΟΣ), I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Toxoplasmosis is a parasitic infection with global distribution caused by the protozoon Toxoplasma gondii. The present study is divided into the preliminary and the basic research. In the preliminary research, 413 serum samples (184 sheep and 229 goats) from organic farms of Péloponnèse and Western Sterea Hellas were tested for IgG antibodies against Τ gondii, by using enzyme-linked immunosorbent assay (ELISA). Blood sampling took place during spring of 2005 and samples were taken from male animals and female that had aborted during the reproductive period of 2004-2005. Significant prevalence of antibodies was the reason that further research of toxoplasmosis in organic farms was conducted. For the basic research, small ruminants' blood samples from organic farms of Péloponnèse, Western Sterea Hellas and the county of Ioannina, were collected during summer of 2006. Blood samples were collected from flocks with cases of abortions during the reproductive period of 2005-2006. Animals were separated into 3 groups: males, females that had abortions during the reproductive period of 2005-2006 and females that did not have abortions during the same period. A total number of 182 sheep sera and 167 goat sera were tested by using the enzyme-linked immunosorbent assay (ELISA). The results showed that antibodies were detected in 38.46% of male sheep, 60.87% of female sheep that had abortions during the reproductive period 2005-2006 and in 54.21% of female sheep that did not have abortions during the same period. Significant difference was determined only between male and female animals (p<0.05). In addition, antibodies were detected in 12.12% of male goats, 14.29% of female goats that had abortions and in 22.35% of female goats that did not have abortions in the reproductive period 2005-2006. There was no significant difference between the results (p>0.05). Seroprevalence in goats was significandy lower than that of the sheep (p<0.05). In animals, aged less than 4 years old, seroprevalence was significantly lower (39.58% for sheep and 13.04% for goats) than that for animals aged more than 4 years old (61.97% for sheep and 24% for goats) (p<0.05). The results of the survey suggest that there is high prevalence of toxoplasmosis both in animals that had aborted and in animals that had not aborted and that there are different species and gender susceptibility. Results also indicate that toxoplasmosis is more common in older animals.